Hydrophobicity Directed Chiral Self‐Assembly and Aggregation‐Induced Emission: Diacetylene‐Cored Pseudopeptide Chiral Dopants - Maurya, Govind P.; Verma, Deepak; Sinha, Aloka; Brunsveld, Luc; Haridas, V. (Angewandte Chemie International Edition, 2022)
Here we delineate simple and tunable hydrophobically driven chiral functional assemblies of diacetylene cored pseudopeptides. These amino acid appended, rigid core dialkynes constitute promising chiral supramolecular building blocks for materials properties engineering. The chiral appended amino acid elements allow for simple tuning of solubility and interaction properties as well as governing chirality, while the central dialkyne core can impart hydrophobically driven assembly and Aggregation Induced Emission (AIE) properties. The self‐assembly of these rod‐like dialkynes can be regulated by tuning the solvent environment, with for example self‐assembly into vesicles in acetonitrile and into helical organization with AIE in a H2O/DMSO mixture. Of additional high interest, these supramolecular materials, themselves devoid of liquid crystal (LC) properties, can induce chirality into non‐chiral LC matrices with high helical twisting power. Designer psuedopeptides with rigid dialkyne core showed hydrophobically driven chiral self‐assembly with AIE. They self‐assembled to vesicles in acetonitrile, while supramolecular helices in 90 % H2O/DMSO. These self‐assembling pseudopeptides devoid of LC property, act as chiral dopants that direct the non‐chiral LC matrix into helical assembly.